EVALUATION OF OUTCOMES FOR NEONATES UNDERGOING SURGICAL INTERVENTIONS (The Research of Medical Science Review, 2024)
11% of the Global Burden of Diseases (GBD) is attributable to neonatal surgical conditions, which require surgical intervention, yet their management has been neglected. On-time surgical interventions are often the keys to better outcomes, achieving quality of life and improving disability. Sepsis control, high dependency unit/intensive care unit (ICU) care and total parenteral nutrition have been shown to improve the outcomes of neonates with surgical conditions, The aim of the study is to evaluate neonatal operative outcome, A descriptive prospective study at Newborn Unit, District Headquarters Hospital Bannu from March 2022 to January 2023. KRP data on maternal age, place of delivery, mode of delivery, age of the newborn at the time of admission, birth weight, surgical condition, co-morbid conditions, treatment outcomes, surgical complications, time-to-initiation of oral feeds post-operatively, antenatal history & laboratory parameters; and length of hospital stay were retrieved and analyzed, Overall, 124 neonates were enrolled, 1.1:1 male female ratio; median age at admission was 2 days (IQR 1, 5). Most were between 2.5–3.9 kg at birth (59.7%). Gastroschisis 33 (26.6%), neural tube defects 25 (20.2%) and ARM 25 (20.2%) were the most common neonatal surgical conditions. The overall mortality was 31.5% Patients attending antenatal clinic were however significantly associated with lower odds of mortality (OR 0.126; 95% CI 0.025–0.6429; p=0.013) while neonatal sepsis, respiratory distress and electrolyte disturbance were significantly associated with increased odds of mortality respectively ([OR 3.4; 95% CI 1.09–22.06; p=0.049]; [OR 4.9; CI 0.91–11.61; p=0.001]; [OR 3.1; CI 1.21–31.60; p=0.029]), The mortality rate of neonates requiring interventions in the study group was 31.5% with median duration of hospital stay of 14.5 days. Among these neonates, the major co-morbid conditions which significantly increased the odds of mortality were neonatal sepsis, respiratory distress and electrolyte abnormality.